Tinjauan Teori Al-Afuww terhadap Produk Makanan Kaki Lima yang Belum Tersertifikasi Halal - Muhamad Naufal Al Dzikri; Panji Adam Agus Putra; Neng Dewi Himayasari (UNISBA Press, 2023)
Abstract. Bandung is a city that is famous for its culinary tourism, both restaurants, cafes, and street food for all types of food and drinks are in the city of Bandung. In principle, in accordance with Law No. 33 of 2014 concerning Guarantees for Halal Products, all entrepreneurs or traders, be it those who sell food or beverage products, must guarantee the halalness of their products through halal certification. This is based on Article 4 of Law no. 33 of 2014 concerning Guarantee of Halal. but in reality there are still many street vendors (PKL) who do not have halal certification for the products they sell. This of course raises concerns for consumers, especially those who embrace Islam, about the dangers of contamination of haram substances in the products they consume. Based on this, the researcher is interested in researching